Biomechanical Comparison of Ponte Osteotomy and Discectomy. Issue 3 (1st February 2015) - Wang, Cheng; Bell, Kevin; McClincy, Michael; Jacobs, Lloydine; Dede, Ozgur; Roach, James; Bosch, Patrick
Abstract : Study Design: Biomechanical cadaver study. Objective: To evaluate the relative effectiveness of Ponte osteotomies for spinal release in deformity correction. Summary of Background Data: Controversy exists as to the role of Ponte osteotomy in deformity correction surgery. Very little has been written about the biomechanical effects of Ponte osteotomy. Past biomechanical studies have been limited to application of forces through endplates, single functional units, or lack of comparison with anterior release. Methods: Twelve fresh-frozen human full thoracic spinal units were tested for motion in axial rotation, flexion/extension, and lateral bending in a custom-designed robotic environment. Testing was repeated after sequential facetectomy and Ponte osteotomy (6 specimens) and compared with partial and full discectomy (6 specimens). Results: Motion in axial rotation is increased 21% by Ponte osteotomy compared with 35% for full discectomy. Anterior displacement of the spinal column, creating lordosis, was increased 15% by Ponte osteotomy and 40% by full discectomy. Posterior displacement of the spinal column, creating kyphosis, was increased 23% by Ponte osteotomy and 89% by full discectomy. Finally, in coronal force application the Ponte osteotomy had virtually no effect (2%) compared with 40% increased motion by full discectomy. Conclusion: Posterior Ponte osteotomy releases produced more motion than facetectomy alone in axial rotation and sagittal correction maneuvers, but had no effect on coronal correction. Anterior discectomy release destabilized spinal column significantly more than posterior releases in all force applications. Despite ample clinical experience demonstrating the effectiveness of posterior-only surgery, the biomechanical effect of Ponte osteotomies is modest. Level of Evidence: N/A Abstract : In a new robotic testing system, the biomechanical effects of anterior and posterior spinal releases on spinal motion in the axial, sagittal, and coronal planes were observed. Anterior releases increased mobility in all 3 planes, whereas posterior releases only affected the axial and sagittal planes.